2015
DOI: 10.1111/gbi.12168
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between lithification and resource availability in the microbialites of Río Mesquites, Cuatro Ciénegas, México

Abstract: Lithified microbial structures (microbialites) have been present on Earth for billions of years. Lithification may impose unique constraints on microbes. For instance, when CaCO3 forms, phosphate may be captured via coprecipitation and/or adsorption and potentially rendered unavailable for biological uptake. Therefore, the growth of microbes associated with CaCO3 may be phosphorus-limited. In this study, we compared the effects of resource addition on biogeochemical functions of microbial communities associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…The microbiomes of microbial mat communities in Lake Clifton, and in particular cyanobacteria in thrombolite‐associated mats, are enriched in genes associated with phosphate limitation (Warden et al., ). Studies of P‐limited microbialites in Cuatro Ciénegas, Mexico, found increased rates of primary production and calcification in P‐addition experiments (Corman, Poret‐Peterson, Uchitel, & Elser, ; Elser et al., ). At Lake Clifton, higher inputs of P by groundwater discharge would therefore increase microbial activity and growth, which is corroborated by our observations of extensive mat growth on thrombolites discharging groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiomes of microbial mat communities in Lake Clifton, and in particular cyanobacteria in thrombolite‐associated mats, are enriched in genes associated with phosphate limitation (Warden et al., ). Studies of P‐limited microbialites in Cuatro Ciénegas, Mexico, found increased rates of primary production and calcification in P‐addition experiments (Corman, Poret‐Peterson, Uchitel, & Elser, ; Elser et al., ). At Lake Clifton, higher inputs of P by groundwater discharge would therefore increase microbial activity and growth, which is corroborated by our observations of extensive mat growth on thrombolites discharging groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…, Corman et al. ); thus, variation in fish‐driven P recycling may be especially important to ecosystem function in these systems. As function of these ecosystems is threatened by the growth of irrigated agriculture in the region, declining groundwater table and spring discharge has reduced temperatures and decreased piscivore abundance in affected locations (Contreras‐Balderas , Minckley , Souza et al.…”
Section: Introductionmentioning
confidence: 99%
“…We tested how variation in consumption affects intraspecific variation in nutrient recycling rates and ratios in a desert fish species, Gambusia marshi, in the Cuatro Ci enegas basin in Coahuila, Mexico. In general, the surface waters of Cuatro Ci enegas are deficient in P and primary production is strongly P-limited (Elser et al 2005, Corman et al 2016; thus, variation in fish-driven P recycling may be especially important to ecosystem function in these systems. As function of these ecosystems is threatened by the growth of irrigated agriculture in the region, declining groundwater table and spring discharge has reduced temperatures and decreased piscivore abundance in affected locations (Contreras-Balderas 1984, Minckley 1992, Souza et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Within the Saprospiraceae family, the genus Haliscomenobacter was represented together with groups of undetermined Saprospiraceae most similar to clones from lithifying microbialites (KP589290 and KP514320, Corman et al . 2016 ), acid mine drainage sediments (KY943160, Ramanathan et al . 2017 ), and a study on Mn-oxidizing bacteria during biofilm formation (AF379685, Kielemoes et al .…”
Section: Resultsmentioning
confidence: 99%